Early Feeding Strategy Mitigates Major Physiological Dynamics Altered by Heat Stress in Broilers - Ahmed Gouda; Hanan Al-Khalaifah; Afaf Al-Nasser; Nancy N. Kamel; Sherin Gabr; Kamal M. A. Eid (Animals, 2024)
Heat stress is one of the stressors that negatively affect broiler chickens, leading to a reduction in production efficiency and profitability. This reduction affects the economy in general, especially in hot and semi-hot countries. Therefore, improving heat tolerance of broiler chicks is a key to sustained peak performance, especially under adverse environmental heat stress conditions. The present study investigated three early feed withdrawal regimes (FWD) as a potential mitigation for thermal stress exposure. A total of 240 unsexed one-day-old Cobb-500 chicks were randomly recruited to one of four experimental groups using a completely randomized design (10 birds × 6 replicates). The experimental groups included the control group with no feed withdrawal (control), while the other three groups were subjected to early feed withdrawal for either 24 h on the 5th day of age (FWD-24), 12 h on the 3rd and 5th day of age (FWD-12), or 8 h on the 3rd, 4th, and 5th day of age (FWD-8), respectively. Production performance was monitored throughout the experiment. Meanwhile, blood and liver samples were taken at the end of the experimental period to evaluate major physiological dynamic changes. Our findings demonstrated that under chronic heat stress conditions, FWD treatments significantly improved broilers’ production performance and enhanced several physiological parameters compared with the control. Serum levels of thyroid hormones were elevated, whereas leptin hormone was decreased in FWD groups compared with the control. Moreover, serum total protein, globulin, and hemoglobin levels were higher, while total cholesterol and uric acid were lower in the FWD groups. Furthermore, FWD groups showed significantly higher antioxidant marker activity with a significantly lower lipid peroxidation level. Immunoglobulin levels, lysozyme, complement factor C3, and liver heat shock protein 70 (HSP70) concentration were also elevated in FWD compared with the control. Also, serum interleukin-1β (IL-1β) and interferon-gamma (IFN-γ) significantly increased with FWD. Based on our findings, early feed withdrawal can be applied as a promising non-invasive nutritional strategy for broilers reared under chronic heat stress conditions. Such a strategy promotes the alleviation of the deleterious effects of heat stress on broiler performance, immunity, and redox status, owing to the onset of physiological adaptation and the development of thermotolerance ability.